Merlin is required for coordinating proliferation of two stem cell lineages in the Drosophila testis - Inaba, Mayu (Sci Rep, 2017)
Although the mechanisms that balance self-renewal and differentiation of a stem cell lineage have been extensively studied, it remains poorly understood how tissues that contain multiple stem cell lineages maintain balanced proliferation among distinct lineages: when stem cells of a particular lineage proliferate, how do the other lineages respond to maintain the correct ratio of cells among linages? Here, we show that Merlin (Mer), a homolog of the human tumor suppressor neurofibromatosis 2, is required to coordinate proliferation of germline stem cells (GSCs) and somatic cyst stem cells (CySCs) in the Drosophila testis. Mer mutant CySCs fail to coordinate their proliferation with that of GSCs in multiple settings, and can be triggered to undergo tumorous overproliferation. Mer executes its function by stabilizing adherens junctions. Given the known role of Mer in contact-dependent inhibition of proliferation, we propose that the proliferation of CySCs are regulated by crowdedness, or confluency, of cells in their lineage with respect to that of germline, thereby coordinating the proliferation of two lineages.